2018
DOI: 10.15611/aoe.2018.2.17
|View full text |Cite
|
Sign up to set email alerts
|

Strategy implementation problems in small and large companies – similarities and differences in light of the research results. Lessons from the polish experience

Abstract: The literature on the strategic management emphasizes the essence and importance of both the good formulation and the proper implementation of the strategy. However, business practice shows that while companies have quite highly developed skills in the area of strategy formulation, at the same time they are characterized by a surprisingly low level of skills in the scope of the effective implementation of the strategy. Various factors that affect the effectiveness of the implementation process are mentioned, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Also, the differences in location sizes and number of managers per location (ranging from 3 to 34) may have influenced the results. Large locations are possibly more bureaucratic (Knill et al, 2019); realizing open strategizing and strategy implementation in a large location may be more difficult than in smaller entities (Kearney et al, 2019;Wolczek, 2018). During the first year of open strategizing adoption, the external stakeholders were not always included in the process.…”
Section: Strengths Limitations and Future Researchmentioning
confidence: 99%
“…Also, the differences in location sizes and number of managers per location (ranging from 3 to 34) may have influenced the results. Large locations are possibly more bureaucratic (Knill et al, 2019); realizing open strategizing and strategy implementation in a large location may be more difficult than in smaller entities (Kearney et al, 2019;Wolczek, 2018). During the first year of open strategizing adoption, the external stakeholders were not always included in the process.…”
Section: Strengths Limitations and Future Researchmentioning
confidence: 99%
“…The investigation based on the designed questionnaire about the degree of impact on the achievement of strategy goals reveals a great interest for building a strategy based on knowledge, than a traditional process approach, although the relevant works seem to indicate different outcomes [20,31,32]. The literature analysis emphasizes the importance of the implementation of the strategy on work performance.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, it cannot be denied that strategy implementation is an integral part of the strategic management process providing several theoretical and practical implications for organizational development (Hourani, 2017). Meanwhile, Wołczek (2018) indicated that the aim of strategy implementation is about allowing strategies formulated by managers and decisions made by executive managers to be a part of the daily business operations. Strategy implementation also entails specific tasks and procedures such as effective allocating of resources, allowing organizational structure to be flexible, developing mechanisms that create communication channels among all organizational departments and support strategic leadership.…”
Section: Strategy Implementationmentioning
confidence: 99%